EXPATRIATE PERFORMANCE AND THE BIG-FIVE PERSONALITY: THE MEDIATING EFFECT OF EXPATRIATE ADJUSTMENT - Fu, Jin Liang (2008)
Personaliti ‘Big-Five’, prestasi Expatriat adalah dua bidang yang kurang ditekankan dalam literature Expatriat.